The Potency of Liquified Smoke as an Antioxidant Used for a Pressure-Cooked Milk Fish - Yuwanti, Sih (Jurnal Teknologi Pertanian, 2005)
The objective of this research was to evaluate the effectiveness of liquified smoke as   an antioxidant used for a pressure-cooked milk fish. Three concentrations of liquified smoke i.e. 2.5%, 5,0% and 7.5% were used. The fish was pressure-cooked in salt solution, dried, soaked in the liquified smoke for a certain period of time and finally redried. An antioxidant activity of liquified smoke was measured by TBA test. The results indicated that liquified smoke was able to act as an antioxidant on a pressure cooked milk fish. The antioxidant activity increased with concentration. An application of liquified smoke at a level of 7,5% may suppress the TBA value of the smoked pressure-cooked milk fish and retain the quality up to 28 days in a cold storage.   Key words : smoked pressure-coooked milk fish,  liquified smoke,  antioxidant